Effect of biosynthesized silver nanoparticle size on antibacterial and anti-biofilm activity against pathogenic multi-drug resistant bacteria - Anas Yahya Ali; Abd-Alrahman Khalid Alani; Barakat O. Ahmed; Layth L. Hamid (OpenNano)
Ag NPs have garnered significant attention in the field of biomedical applications due to their antibacterial, antifungal, antiviral, anti-inflammatory, and antiangiogenic effects. The present study aimed to establish a simple, reliable, cost-effective, and environmentally friendly approach for the synthesis of Ag NPs in different sizes using extracts from Syzygium aromaticum and Laurus nobilis and study the relationship between the size of Ag NPs and their antibacterial and anti-biofilm effectiveness. The synthesized Ag NPs were extensively characterized using various techniques, such as XRD, SEM, UV–vis and FTIR. Importantly, the study evaluated the antibacterial and anti-biofilm activities of Ag NPs in two different size (12 nm and 45 nm) against MDR and biofilm-producing pathogenic bacteria, including Kocuria rosea, Staphylococcus sciuri, and Staphylococcus lentus. The antibacterial activity of the larger Ag NPs-SA (45 nm) ranging between 14–25 mm while for the smaller Ag NPs-LN (12 nm) ranging between 26–48 mm against pathogenic bacteria. The MIC values for Ag NPs-LN were between 16 - 32 µg/ml while for Ag NPs-SA were 64 µg/ml. The MIC value of the Ag NPs decreased as their size decreased, indicating higher potency against the tested bacterial strains. Furthermore, the smaller Ag NPs-LN exhibited a higher rate of biofilm inhibition that reach 88% compared to the larger Ag NPs that reach 70%. This study provides novel evidence that the enhanced antibacterial and anti-biofilm activities of Ag NPs are directly correlated with their decreased nanoscale size. These findings highlight the potential of Ag NPs as a promising adjuvant in the management of bacterial infections, particularly those involving MDR and biofilm-producing pathogens, which pose a significant challenge in clinical settings.